Indications for pancreaticoduodenectomy affected postoperative outcomes in octogenarians. Issue 1 (31st August 2020) - Okabayashi, Takehiro; Sui, Kenta; Murokawa, Takahiro; Kimura, Jiro; Iwata, Jun; Morita, Sojiro; Iiyama, Tatsuo; Shimada, Yasuhiro
Abstract: Aims: The safety and efficacy of pancreaticoduodenectomy (PD) in patients over the age of 80 years remain controversial. We aimed to examine post‐PD outcomes and to determine the age limit for PD. Methods: Patients were divided into two subgroups: the younger (<80 years) group and octogenarian (≥80 years) group. We retrospectively evaluated the clinical benefit of PD for periampullary diseases in the younger and octogenarian groups, focusing on short‐ and long‐term outcomes. Results: From March 2005 to December 2018, 586 consecutive surgically curable patients with diagnosed periampullary diseases were studied, among whom 122 (20.8%) were ≥80 years old. The general preoperative physical condition (G8 screening, instrumental activities of daily living, and Charlson comorbidity index) and nutritional status were significantly worse in the octogenarian group. However, there were no significant differences between the younger and octogenarian groups in postoperative severe complication rates (34% vs 36%) or perioperative mortality rates (1.5% vs 0.0%). We observed significantly poorer 3‐, 5‐, and 10‐year overall survivals in the octogenarian group than in the younger group ( P  = .007). In the younger group, the main cause of death (89.6%) was cancer recurrence. However, only 60% of patients in the octogenarian group developed and died from cancer recurrence. Increased neutrophilic/lymphocyte ratio and elevated Controlling Nutritional Status score were associated with worse outcomes. Conclusions: It is important to carefully determine the indication for PD in octogenarian patients with periampullary diseases, although patient age over 80 years should not be a contraindication for PD. Abstract : The safety and efficacy of pancreaticoduodenectomy (PD) in patients over the age of 80 years remain controversial. Although our findings showed that the general preoperative condition and nutritional status were significantly worse in the octogenarian group, there were no significant differences between both groups regarding postoperative severe complication rates or perioperative mortality rates. The instrumental activities of daily living (IADL) scale in octogenarian patients might be preserved enough high functioning, although IADL scale in the octogenarian group was significantly lower than that in the younger group. The 3‐, 5‐, and 10‐year overall survival were significantly worse in the younger group than in the octogenarian group. In the younger group, the main cause of death (89.6%) was cancer recurrence. However, only 60% of patients in the octogenarian group developed and died from cancer recurrence.